If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(-3x + -8) + -4x + 8 = 0 Reorder the terms: -4(-8 + -3x) + -4x + 8 = 0 (-8 * -4 + -3x * -4) + -4x + 8 = 0 (32 + 12x) + -4x + 8 = 0 Reorder the terms: 32 + 8 + 12x + -4x = 0 Combine like terms: 32 + 8 = 40 40 + 12x + -4x = 0 Combine like terms: 12x + -4x = 8x 40 + 8x = 0 Solving 40 + 8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + 8x = 0 + -40 Combine like terms: 40 + -40 = 0 0 + 8x = 0 + -40 8x = 0 + -40 Combine like terms: 0 + -40 = -40 8x = -40 Divide each side by '8'. x = -5 Simplifying x = -5
| 15/30=6/x | | -100=n+8 | | -100=n+8 | | -100=n+8 | | -100=n+8 | | 15/30=6/x | | -100=n+8 | | -100=n+8 | | -100=n+8 | | -100=n+8 | | -8x+3+3x=13 | | 7x=3(3x-4) | | 7x+5(4-2x)=5 | | (x-35)+90+43=180 | | (8x+4)(8x-4)=y | | -6x+7(2x+6)=142 | | -90-6x=48-12x | | -100=n+8 | | 7x+5(4-2x)=5 | | (8x+4)(8x-4)=y | | -4(-3x-8)-4x+8= | | (x-35)+90+43=180 | | 6(p+8)= | | -90-6x=48-12x | | -4(-3x-8)-4x+8= | | 6(p+8)= | | x+28500-y=371500 | | 6(p+8)= | | x+28500-y=371500 | | 15/30=6/x | | 7x=3(3x-4) | | 7x=3(3x-4) |